Expression of the serine protease inhibitor neuroserpin in cells of the human myeloid lineage - Kennedy, Sarah A.; van Diepen, Angela C.; van den Hurk, Cecilia M.; Coates, Leigh C.; Woo Lee, Tet; Ostrovsky, Lena L.; Miranda, Elena; Perez, Juan; Davies, Mark J.; Lomas, David A.; Dunbar, Rod P.; Birch, Nigel P. (Thrombosis and Haemostasis, 2007)
Myeloid progenitors in the bone marrow differentiate into most of the major cell types of the immune system, including macrophages and dendritic cells. These cells play important roles in both innate and adaptive immunity. They express a number of proteases and protease inhibitors including members of the serine proteinase inhibitor or serpin superfamily. In this study we report the differential expression of neuroserpin in cells of the human myeloid lineage. Neuroserpin was highly expressed and secreted following the differentiation of monocytes to macrophages and dendritic cells. Activation of dendritic cells with lipopolysaccharide resulted in increased neuroserpin mRNA levels but no neuroserpin secretion. Confocal immunofluorescence microscopy showed neuroserpin was differentially localised in human myeloid cells. In macrophages and dendritic cells it was concentrated in vesicles located in close proximity to the plasma membrane. The majority of activated dendritic cells also exhibited an intracellular focal concentration of neuroserpin which co-localised with the lysosomal/late endosomal marker LAMP-1. As neuroserpin inhibits tissue plasminogen activator, a comparative analysis of tPA and plasminogen activator inhibitor-1 (PAI-I) expression was undertaken. This analysis revealed differential expression of PAI-I and neuroserpin suggesting they may have different functions in human immune cells.
Keywords: Monocytes; serpin; dendritic cells; macrophages; tissue plasminogen activator